Biologic Treatments of Psoriasis: An Update for the Clinician - Brownstone ND (Dove Medical Press, 2021)
Nicholas D Brownstone, Julie Hong, Megan Mosca, Edward Hadeler, Wilson Liao, Tina Bhutani, John Koo University of California, San Francisco, Department of Dermatology, Psoriasis and Skin Treatment Center, San Francisco, CA, USACorrespondence: Nicholas D BrownstoneUniversity of California, San Francisco, Department of Dermatology, Psoriasis and Skin Treatment Center, 515 Spruce Street, San Francisco, CA, 94118, USATel +1 415-476-4019Fax +1 415-502-4126Email Nicholas.Brownstone@ucsf.eduAbstract: The advent of biologic agents within the past two decades has dramatically improved the treatment of psoriasis and psoriatic arthritis. Given that there now exists 11 FDA approved biologic options available for psoriasis, with more in the pipeline, the therapeutic armamentarium has been greatly enhanced. However, the fact that there are so many available options has also caused confusion for providers. Therefore, this manuscript deliberately focuses on the most clinically useful facts (such as efficacy and safety data) about each and every FDA approved biologic agent (including pipeline agents) for psoriasis. Moreover, among the clinically relevant facts, this manuscript purposely emphasizes the unique merits and demerits of each agent to make it easier for the provider to select which one of these many options is the best for the particular patient on hand. The goal of this manuscript is to aid the busy practicing dermatologist in becoming more adept at using these agents with the ultimate aim of improving patient care.Keywords: biologic therapy, psoriasis, IL-17, TNF-alpha, IL 12/23, psoriatic arthritis, IL-23